The Role of the Justice Collaborator in A Premeditated Murder Crime - Muhamad Romdoni; Aldestianah Putri Abu Bakar (LEGAL BRIEF, 2022)
Justice collaborators are perpetrators of crimes willing to work with law enforcement to dismantle a crime or case that is considered complex and major. In criminal acts of murder that are organized and carried out by several people, the role of a justice collaborator is needed to reveal the role of each perpetrator. This study employs a normative juridical approach with statutory and case studies. According to the findings of this study, the role of a justice collaborator in the criminal act of organized murder committed by multiple perpetrators is critical in terms of providing information to law enforcement officials, what is the chronology of the beginning of the loss of life, what tools were used by the perpetrators in killing someone, the place where the loss of life occurred, to the extent of exposing the perpetrators who were involved in the loss of life so that the crime can be completed and not stop at the perpetrators who played a minimal role. Then, under law No. 31 of 2014, witnesses and victims are protected, and the requirements for becoming a justice collaborator, according to SEMA No. 4 of 2011, are that one of the perpetrators of a crime, but not the main actor in a crime, provides information as a witness in the judicial process, providing significant evidence, and uncovering actors who have a larger role.